Inspiring Wednesday, Ciputra University Best Practice in Shaping Entrepreneurs in Higher Education - Antonio, Tony (Universitas Ciputra Surabaya, 2012)
Ciputra University has a core focus on entrepreneurship and always emphasized entrepreneurships education in a contextual way. This paper shares the best practices of Entrepreneurships Education program that’s being run at Ciputra University. The program known as “Inspiring Wednesday.” In this program, for one day each week the study will be dedicated solely to entrepreneurship topics. It is conducted through the entire campus starting with the students from the first semester all the way to the fifth semester. The program offers the students a combination of real-live learning experience along with skills which are useful assets for aspiring entrepreneurs. The Entrepreneurship education is carried out by both lecturer as entrepreneur enabler and professional entrepreneurs, called as entrepreneur in residence, in order to achieve University’s objectives. This paper covers the rationale, methods, results, and evaluation of the inspiring Wednesday in Ciputra University.